Teaching Leadership in UAE Business and Education Programmes: A Habermasean Analysis within an Islamic Context - ELKALEH, EMAN (2015)
The thesis uses Habermasean critical theory, focussing on his theory of knowledge and human interests and communicative action model in particular, to investigate leadership curricula in selected UAE business and education programmes and examine the extent to which they are derived from and linked to students’ cultural and Islamic values. The study is conducted in response to scholars’ calls for developing leadership models and practices that integrate traditional and international knowledge and perspectives to mitigate the dominance of Western theories and values that threaten Islamic and cultural identity over the curriculum. It aims to start a dialogue between Western and Islamic sources of knowledge and to select the practices that work best in any particular society given its unique cultural and religious values. This study employs a mixed methods approach that takes classical pragmatism as its philosophical foundation and critical theory as a theoretical lens. Data is collected in four sequential phases using critical discourse analysis of course materials, class observations, student survey and faculty interviews with qualitative and quantitative methods given equal importance and weight during data collection and analysis. Results were integrated at the interpretative level and abductive reasoning was used as the logic of justification. Results show that there are increasing efforts to incorporate cultural and Islamic values into the curriculum. However, the curriculum is still mainly dominated by Western theories and models of leadership, especially in the leadership courses offered by business schools, mainly because of the lack of English resources and theories on UAE and Islamic models of leadership. There was a significant difference between business and education leadership courses: education courses tended to include more materials on the UAE and Islamic leadership than did business courses. Thus, education students viewed the curriculum as more relevant to their cultural and Islamic values than business students did. It also found that faculty played a significant role in adapting the curriculum to students’ cultural and Islamic values. Those who were either Muslim or came from a multicultural environment (e.g. VI Australia, Canada, New Zealand) where they taught Muslim students tended to include more materials on Islamic and UAE leadership models than those who were not exposed to similar experiences or possessed the same knowledge about Islam. Students, while highly appreciative of the genuine efforts exerted by faculty to incorporate Islamic and cultural materials into the curriculum, believed that these efforts are not enough as Islamic history is very rich and more materials on UAE and other Muslim leaders can be further added to the curriculum. Faculty attributed the limited use of Islamic and cultural materials to the lack of published work on Islamic leadership and the UAE, in one hand, and to the academic standards that they have to meet for the purposes of international accreditation, on the other. Based on these findings, the thesis offers a model that is derived from Habermas’ theories of knowledge and human interests and communicative action to develop a culturally relevant approach to leadership teaching. The model embraces a holistic approach that appreciates and recognises the significant contributions of Western and indigenous knowledge and encourages openness to mutual learning between both traditions.